Ex-vivo longitudinal tibial growth patterns of rat: gross and histologic features - Abubakar, Adamu Abdul; Khan, Muhammad Shuaib; Mohamed Mustapha, Noordin; Tengku Ibrahim, Tengku Azmi; Mohamad Yusof, Loqman (2015)
Chondrocytes undergo as much as 10 to15-fold increase in volume during endochondral ossification. The volume increase has been demonstrated to be single most significant variable in understanding the qualitative aspect of long bone growth. The objective of the study was to determine and compare the gross growth rate patterns of long bone and chondrocyte cells density at different growth plate zone (GPZ) in 7 to 15 day-old rat’s tibia. Forty five young Sprague-Dawley rats, age 7 to15 day-old were divided into nine age groups. Five rats were allocated to each age group. The rats were sacrificed and the tibia was harvested in standard dissecting media. The tibial lengths were measured before and after incubation at 24, 48 and 72 hours in standard culture media. We observed that there was significant differences (P=0.0001) in bone length growth among age groups under at different incubation periods. Histological sectioning was possible in 7 to 13 day-old rat’s tibia, while sectioning was slightly difficult in 14 and 15 day-old tibia. Significant difference (P=0.001) in chondrocytes density in all the three zones of GP (PCZ, EHCZ and LHCZ)] among different age groups at different incubation periods was observed. We conclude that the tibia from 10 day-old rats can produce maximum growth rate for in-vitro cultivation. Histological sectioning of tibial bones can be carried without the need for decalcification in P7 to P13 rats.